2018
DOI: 10.1002/fut.21920
|View full text |Cite
|
Sign up to set email alerts
|

From funding liquidity to market liquidity: Evidence from the index options market

Abstract: This study examines the relationship between funding liquidity and market liquidity using daily data on the S&P 500 index options. We find that options market liquidity is positively correlated with funding liquidity after controlling for market uncertainty. Further analysis reveals that the positive relationship between funding liquidity and market liquidity in the options market is mainly driven by short‐term and deep out‐of‐the‐money options. Our results remain robust after controlling for the confounding e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Second, sentiment shocks negatively impact futures market liquidity, indicating that investors prefer futures contracts when economic sentiment is pessimistic. We confirm that the sentiment effect is significant even after controlling for the impact of implied volatility, which is discovered by Liu et al (2018). Third, optimistic (pessimistic) sentiment reinforces (weakens) the negative relationship between funding liquidity and futures market liquidity.…”
supporting
confidence: 72%
See 3 more Smart Citations
“…Second, sentiment shocks negatively impact futures market liquidity, indicating that investors prefer futures contracts when economic sentiment is pessimistic. We confirm that the sentiment effect is significant even after controlling for the impact of implied volatility, which is discovered by Liu et al (2018). Third, optimistic (pessimistic) sentiment reinforces (weakens) the negative relationship between funding liquidity and futures market liquidity.…”
supporting
confidence: 72%
“…They also provide evidence that the two markets respond interactively to funding liquidity shocks. Liu et al (2018) also find that the effect of funding liquidity, proxied by the Treasury-Eurodollar (TED) spread, significantly and positively forms market liquidity. Deuskar and Johnson (2021) emphasize the role of local funding services over interest rate changes, in contributing to funding availability for investors and shaping liquidity in the government bond market.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…Guo et al (2017) provided strong support for the literature's conjecture that market wide liquidity is an important asset pricing risk factor. Liu et al (2018) also found that the options market liquidity was positively correlated with funding liquidity after controlling for market uncertainty. The positive relationship between funding liquidity and market liquidity in the options market was mainly driven by short-term and deep out-of-the-money options.…”
Section: Introductionmentioning
confidence: 81%